Arahan Pemanfaatan Lahan Permukiman Di Kawasan Rawan Bencana Longsor (Studi Kasus : Di Kabupaten Banjarnegara) - pratama, gigit; herawati, susetya (Journal of Urban and Regional Development Studies, 2023)
This research was conducted in the Northern Region of Banjarnegara Regency, this research method uses quantitative analysis methods and qualitative descriptive analysis using ArcGIS software, namely by analyzing the landslide hazard index, landslide hazard vulnerability index, land capability, including microorganism land, reflecting the organization's land needs. The research results found that the landslide hazard level was low, medium and high with a total area of ​​high landslide hazard class of 5,576 Ha, medium hazard area of ​​5,245 Ha and low hazard area of ​​17,238 Ha. The threat level for landslides has low, medium and high vulnerability levels with a total area of ​​5,871 Ha for low vulnerability, 4,815.7 Ha for medium vulnerability and 133.6 Ha for high vulnerability. while the potential for lives exposed to the danger of landslides is 21,763 people, potential physical loss IDR 116,600,000,000,-, potential economic loss IDR 19,602,528,251,924,-, and potential environmental loss with a total area of ​​8,198 Ha. The land capacity in the northern region of Banjarnegara Regency is in the medium development capacity zone class with an area of ​​4,689 Ha and sufficient development capacity with an area of ​​33,695 Ha. Settlement Land Suitability has a very suitable category of 1,482 Ha (4%), a suitable category of 16,576 Ha (43%), a less suitable category of 19,454 Ha (51%), and an unsuitable category of 871 Ha (2%). The projection of the organization's land needs in 2040 shows that the organization's land needs have a total area of ​​1,574 Ha and based on the analysis of the results of the organizational development land use direction in the northern area of ​​Banjarnegara Regency, it has a total area of ​​5,790 Ha, with a level of conformity with the organization's spatial pattern plan in the SUITABLE category with an area of ​​1,263 Ha (52%) and the unsuitable category is 1,181 Ha (48%). Landslide disaster mitigation directions for organizational areas located within the landslide Disaster Prone Zone (ZRB), namely for relocation, are 10 Ha (2%), area protection directions are 132 Ha (23%) and adaptation directions are 436 Ha (75%) . Based on the results of the analysis, the direction of organizational land use in the northern region of Banjarnegara Regency is still sufficient with the availability of surplus land of 4,216 Ha.